An Encyclopedia Coverage of Compiler’s, Programmer’s & Simulator’s for 8051, PIC, AVR, ARM, Arduino Embedded Technologies - Anand Nayyar (International Journal of Reconfigurable and Embedded Systems (IJRES), 2016)
In today’s world, everything from small needle to airplane engineering is surrounded by embedded systems. Embedded System technology not only lays foundation for development but is also acting as Backbone for mankind in almost in every area of science, engineering, research and daily living. The world of embedded systems is mainly surrounded by: Microcontrollers and Microprocessor’s. To work in the area of Embedded Systems design and development is both interesting and challenging- Interesting in the sense, as everything is getting intelligent, advanced and feature rich day by day and the embedded system’s field is progressing by leaps and bounds. But challenging in the way, that resources are very limited in terms of design and implementation. The most important crucial challenges nowadays in front of embedded system engineers are- Which programmer to Use? Which compiler to use for source code development? Which simulator to use to simulate the overall behavior of system? As every compiler, programmer and simulator has distinct features, so selecting the best one as per one’s requirement has always remained a challenge. The main aim of this research paper is to overcome that difficulty by providing the researchers and embedded system engineers an encyclopedic platform of compilers, programmers and simulators for all sorts of embedded system technologies like 8051, PIC, ARM, AVR and Arduino so that choosing of the best platform in terms of compiler, programmer and simulator can become easy and time saving for everyone working in this area.